What is architectural management? Towards a pragmatic definition. Issue 2 (16th March 2015) - Alharbi, Mohammed; Emmitt, Stephen; Demian, Peter
Abstract : Purpose: – The purpose of this paper is to provide a pragmatic definition of architectural management (AM) derived from systematic research. Design/methodology/approach: – A triangulated approach to data collection was employed, comprising a number of sequential stages. First, a literature review was carried out to analyse the previous attempts to define the term. Then, a preliminary survey was conducted (online questionnaire) to capture the current interpretations of the term. After that, a new definition was formulated based on analysing and synthesising the collected data. The fourth stage was focused on examining the consistency of the new definition through the perspectives of architectural researchers and practitioners. The final stage was refining the definition based on the feedback. Findings: – After following a pragmatic approach for constructing a new definition of AM; and based on the results of the several testing stages, it was found that AM is associated with the strategic management of the architectural office and its individual projects; and it is responsible for value design and delivery for its adopter and for the different types of stakeholders. Research limitations/implications: – Although there was some quantitative testing in addition to the qualitative data the response rate was low in terms of the population of UK architectural practices. Originality/value: – The outcome is the first definition of AM grounded in research. The research is unique in terms of reviewing the scope and limitations of the previous definitions of AM. Based on the research findings, the new definition of AM was found to offer an accepted description of AM that can be used by both researchers, educators and practising architects. The definition provides a common understanding (vocabulary) for those working in the area of AM.